Applying Theory to Explain the Influence of Factors External to an Organization on the Implementation of an Evidence-Based Intervention - Leeman, Jennifer; Wangen, Mary; Kegler, Michelle; Lee, Matthew; O'Leary, Meghan C.; Ko, Linda K.; Fernández, María E.; Birken, Sarah A. (Frontiers in Health Services, 2022)
Despite its widely acknowledged influence on implementation, limited research has been done on how the external environment (i.e., outer setting) determines when organizations adopt and implement new interventions. Determinant frameworks identify several outer setting-level factors such as funding streams, inter-organizational relationships, and peer pressure. However, these frameworks do not explain how or why outer-setting factors influence implementation. To advance research in this area, we argue for the importance of deriving theory-based propositions from organization theory to explain how outer setting factors influence organizations. Drawing on the work of the Organization Theory in Implementation Science (OTIS) project, we identified 20 propositions from five classic organization theories—Complexity Theory, Contingency Theory, Institutional Theory, Resource Dependence Theory, and Transaction Cost Economics. We then applied those propositions to hypothesize relationships among outer setting factors, implementation strategies, and implementation outcomes in five case studies of evidenced-based tobacco control interventions. The five case studies address the implementation of smoke-free policies, community health worker-led tobacco education and cessation programs, 5 A's (Ask, Advise, Assess, Assist, and Arrange), point-of-sale tobacco marketing policy interventions, and quitlines. The case studies illustrate how propositions may be used to guide the selection and testing of implementation strategies. Organization theories provide a menu of propositions that offer guidance for selecting and optimizing high-leverage implementation strategies that target factors at the level of outer setting. Furthermore, these propositions suggest testable hypotheses regarding the mechanisms underlying the influence of outer-setting factors on how and why organizations adopt and implement interventions.